Understanding the concept of health literacy: A strategy to improve nursing practice - Cecilia Bukola Bello; Oladayo Damilola Akinwale; Mayowa Grace Elemile (Journal of Integrative Nursing)
Health literacy (HL) is an effective approach for improved health status and measures the capacity of individuals to engage in health promotion and disease prevention activities as low HL constitutes a global problem in health-care delivery. Nurses play a significant role in providing adequate information to the client and as such it becomes imperative for them to understand the concept of HL. Clinical approach of HL refers to ability to utilize literacy skills in relation to appointments, prescriptions, and instructions for self-management. Public health approach presents HL as means of empowering individuals to take control of their health and factors that influences health. HL is a hierarchy of skills that can be assessed and managed through health education and effective communication. Nurses’ understanding of the concept of HL and strategies to reduce HL demands is crucial to delivery of effective nursing practice. This review will provide a clear understanding of the concept of HL which is essential for nurses to effectively educate patients and provide holistic care. More so, nurses will be able to assess literacy level of the patients, plan and develop better educational program tailored to patients’ level of literacy. This could invariably improve patients’ comprehension and adherence to treatment plans and overall health outcomes.